3‐2: Invited Paper: Color on Demand – Color‐Tunable OLEDs for Lighting and Displays. Issue 1 (May 2017) - Fröbel, Markus; Schwab, Tobias; Kliem, Mona; Lenk, Simone; Leo, Karl; Reineke, Sebastian; Gather, Malte C.
Abstract : A device concept for highly efficient OLEDs is introduced that allows to tune the emission color of the device over a broad range of the CIE color gamut. The approach exploits the different polarities of the positive and negative half‐cycles of an alternating current driving signal to independently address two vertically stacked emission units with complementary color. Ultrathin metal electrodes fabricated by a wetting layer approach are used to achieve good electrical contact to each stack with minimal impact on optical performance.